Affordability of essential medicines: The case of fluoride toothpaste in 78 countries. - Athanasios Gkekas; Benoit Varenne; Nicole Stauf; Habib Benzian; Stefan Listl (PLoS ONE, 2022)
Background Fluoride toothpaste (FT) has recently been included in the WHO Model List of Essential Medicines. Whereas it is essential for preventing dental caries, its current affordability around the globe remains unclear. This study aimed to analyse the affordability of FT in as many as possible countries worldwide, to capture the extent of variations in FT affordability between high-, middle- and low-income countries. Methods A standardized protocol was developed to collect country-specific information about the characteristics of the cheapest available FT at a regular point of purchase. 82 members of the WHO Global Oral Health Network of Chief Dental Officers (CDOs), directors of WHO Collaborative Centres and other oral health experts collected data using mobile phone technology. In line with established methodologies to assess affordability, the Fluoride Toothpaste Affordability Ratio (FTAR) was calculated as the expenditure associated with the recommended annual consumption of FT relative to the daily wage of the lowest-paid unskilled government worker (FTAR >1 = unaffordable spending on fluoride toothpaste). Results There are significant differences in the affordability of FT across 78 countries. FT was strongly affordable in high-income countries, relatively affordable in upper middle-income countries, and strongly unaffordable in lower middle-income and low-income countries. The affordability of FT across WHO Regions was dependent upon the economic mix of WHO Regions' member states. Conclusion FT is still unaffordable for many people, particularly in low-income settings. Strategies to improve the universal affordability of FT should be part of health policy decisions in order to contribute to reducing dental caries as a global public health problem.